To Analysis Various Factors as a Conclusion for the Success and Failure of the Village Panchayats - Singh, Lokendra Kumar (Integrated Journal for Research in Arts and Humanities, 2023)
The present study counduted in Baghpat district in 2014. District Baghpat is one of the district of Uttar Pradesh, to measure the opinion of respondents found Majority i.e. 89.67%, 85.00%, 70.33% and 54.00% respondents have mentioned that they are aware regarding, construction of house, toilet for poor people, construction of drainage, Panchayat Building and boundary wall of school, as a rural development work done by the Village Panchayat. As regards health and sanitation work data reveals majority i.e. 85.33%, 68.67%, 54.67% and 53.33% respondents have shown their awareness regarding work done by the Village Panchayat, vaccination for the prevention of polio, diarrhea and smallpox, de siltation of Village ponds, specially making Villagers to aware family planning and Removal of waste product respectively. Maximum i.e. 60.67%, 54.67%, 45.67%, 40.00% and 39.33% respondents were well acquainted so far the work for economic development by the Village Panchayat is concerned with special reference to arrangement of loan and pension for the poor, to trained village people for self employment, to organized self help group, to start fish production in village ponds, and to give village land on lease. Further revealed majority i.e. 70.33%, 63.00%, 61.33% 55.33% and 54.33% respondents in case of Gram Sabha and Village Panchayat had shown unhappiness so far as the work for agriculture development is carried out by the Village Panchayat with special reference to arrangement for improved agriculture equipment for villager, to arrange meetings of block officers and K.V.K. in village, to arrange for soil testing, arrange for seeds, fertilizer on cheap rate from co-operative store for villager and to arranged for vaccination to prevent animal disease of the respondents.